Adoption of digital forensic by Malaysian large enterprises: a conceptual framework / Siti Nuur-Ila Mat Kamal, Nor Diana Abd Rahman and Nor Rashidah Mohamed - Mat Kamal, Siti Nuur-Ila; Abd Rahman, Nor Diana; Mohamed, Nor Rashidah (UiTM Cawangan Johor, 2019)
The increased use and dependency on ICT and technological advancement have caused a big challenge to today’s businesses and modern organization. This paradigm has seen the rise in the statistics of cybercrime and digital incidents cases involving major losses and collapse of businesses and firms. In addressing and preparing the organization for incidents of this nature, the adoption of digital forensic (DF) is necessitated. However, the adoption of DF in Malaysian organisations is unfavourable. This study reviewed the literature to identify the probable factors that influence organisation’s decision to adopt DF and proposed a framework for an in-depth investigation into possible factors influencing the adoption of DF in an organisation. In doing so, possible policy and academic implications will emerge which form the basis for implementation and further study.